Escherichia coli RecG and RecA proteins in R-loop formation. - Hong, X (1995)
Escherichia coli rnhA mutants devoid of RNase HI exhibit constitutive stable DNA replication, cSDR, which is thought to be initiated from R-loops stabilized in the absence of RNase HI. We found that a combination of an rnhA and a recG mutation is lethal to the cell. recG mutations that inactivate the helicase activity of RecG protein and inhibit reverse branch migration of Holliday junctions impart phenotypes resembling those of rnhA mutants. Thus, recG mutants display cSDR activity, and recG polA double mutants are inviable as are rnhA polA double mutants. These results suggest that the RecG helicase has a role in preventing R-loop formation. A model that R-loops are formed by assimilation of RNA transcripts into the duplex DNA is discussed. The model further postulates that RecA protein catalyzes this assimilation reaction and that RecG protein counteracts RecA in this reaction, resolves R-loops by its helicase activity, or does both.